2016
DOI: 10.1037/cdp0000089
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of interminority extended contact: The role of affective and cognitive mediators.

Abstract: Objective: Research on intergroup contact and prejudice reduction has dedicated little attention to relations between minority groups. We examined whether interminority extended contact, that is, the knowledge that a member of the minority ingroup has a friend from the minority outgroup, is associated with positive outgroup attitudes. Affective (outgroup empathy and outgroup trust) and cognitive (ingroup norm) mediators were considered. Method: Two correlational studies were conducted. Study 1 (N = 640, 50% fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Specifically, across both studies, we found evidence that direct contact experiences involved all three affective mediators that we considered, i.e., intergroup anxiety, empathy and trust. For extended contact, in Study 1 we found outgroup trust to be the only significant mediator, while in Study 2 intergroup anxiety and empathy also contributed to the mediated effects of positive extended contact (see also Paolini et al, ; Tam et al, ; Visintin et al, ). With regard to parasocial contact through mass media, the role of affective mediators was more marginal, although trust emerged again as the crucial mediator.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Specifically, across both studies, we found evidence that direct contact experiences involved all three affective mediators that we considered, i.e., intergroup anxiety, empathy and trust. For extended contact, in Study 1 we found outgroup trust to be the only significant mediator, while in Study 2 intergroup anxiety and empathy also contributed to the mediated effects of positive extended contact (see also Paolini et al, ; Tam et al, ; Visintin et al, ). With regard to parasocial contact through mass media, the role of affective mediators was more marginal, although trust emerged again as the crucial mediator.…”
Section: Discussionmentioning
confidence: 73%
“…While the mediational roles of negative emotions such as intergroup anxiety and of positive effects such as empathy and trust toward the outgroup are well‐established with respect to the effects of direct contact, their role in the relationship between indirect intergroup contact and prejudice needs to be further addressed. Concerning extended contact, there is some evidence that extended contact, similarly to direct contact, reduces intergroup anxiety (e.g., Mereish, & Poteat, ; Paolini, Hewstone, Cairns, & Voci, ) and increases outgroup trust (e.g., Visintin, Brylka, Green, Mähönen, & Jasinskaja‐Lahti, ) and empathy (Turner et al, ; Visintin et al, ). For mass‐mediated contact, the parasocial contact hypothesis (Schiappa et al, ) suggested that people process media experiences similarly to direct experiences: Thus, contact through the mass media may change emotional reactions toward the outgroup in the same way that direct contact does.…”
Section: Mediating Mechanisms Of the Relationship Between Contact Andmentioning
confidence: 99%
“…Hence (positive) extended contact should result in perceptions of in‐group and out‐group norms supporting cross‐group interactions, which in turn should be positively associated with out‐group attitudes. Research has supported in‐group and out‐group norms as two critical mediators of extended contact (Davies, Wright, Aron, & Comeau, ; De Tezanos‐Pinto, Bratt, & Brown, ; Turner, Hewstone, Voci, & Vonofakou, ; Visintin, Brylka, Green, Mähönen, & Jasinskaja‐Lahti, ). However, evidence for in‐group and out‐group norms has been primarily provided for majority members.…”
Section: Mediators Of Extended Contactmentioning
confidence: 99%
“…Clearly, there is a need for future studies taking into consideration both majority and minority participants and formally testing moderation by group status for both positive and negative extended contact. In addition, future studies may also consider moderation by group status in minority groups, taking into account the relative status within the larger status hierarchy (Visintin et al, ).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Some researchers have emphasized the distinction between merely knowing that ingroup friends have outgroup friends and observing intergroup contact between members of the in-and outgroupthe former type of indirect contact referring to extended contact and the latter to vicarious contact (Dovidio, Eller, & Hewstone, 2011;Vezzali et al, 2014). Extended contact is often operationalized by asking people about the prevalence of direct outgroup contact and friendships among their friends (e.g., Turner, Hewstone, & Voci, 2007;Visintin, Brylka, Green, Mähönen, & Jasinskaja-Lahti, 2016). Vicarious contact, in turn, is most often studied experimentally so that the intergroup contact that is being observed is manipulated (Vezzali et al, 2014).…”
Section: Improving Ethnic Attitudes Through Vicarious Contactmentioning
confidence: 99%